Phenomenology of scales on summits: sensations, consciousness and literary language at the trial of the mountain in Manuel Rojas and Gary Snyder (ENTHYMEMA, 2023)
This article focuses on a selection of narrative and poetic works by the Chilean Manuel Rojas and the American Gary Snyder, both mountaineers and driven by the concern of capturing, in literary language, the human being's venturing into the wild environment of the mountain, and his plunge into a state of perceptual alertness and lucid contemplation in the face of the disparate scales that are revealed there. Framed in scale theory (DiCaglio, Jue, Horton, Cueto) and in the concept of adventure (Agamben), the hypothesis postulates that the human experience of scales in the mountain environment is translated into an expansion of consciousness, deriving, depending on the case, in a dispossession of the self or in an obfuscated intuition of the mortal danger that is proposed as exemplum to the reader, and in a modification of the literary language itself that accompanies and makes the adventure possible.
Keywords: Manuel Rojas; Gary Snyder; Scale Theory; Mountain; Conscience